Diffusion of environmental and social sustainability practices across the supplier base - Pimenta, Handson Claudio Dias (Cranfield University, 2016)
Significant literature on sustainable supply chain management exists but there is a lack of theory explaining diffusion of sustainability practices within the supplier base led by manufacturing firms. In particular diffusion theory is insufficiently developed to characterise the development of sustainability practices in suppliers. The purpose of this research is to establish the conditions for enhancing the diffusion of environmental and social sustainability practices across the supplier base from the buying firms’ perspective. The research design is based on a theory building strategy. The data analysis was carried out based on a triangulation of different sources of data (e.g. 30 interviews with directors or managers of four sustainability leading manufacturing firms from the beverage, cosmetic and textile sector, and an extensive array of documents) and cross-case analysis and application of diffusion of innovation theory (DoI). This research identified environmental and social practices diffused through supplier selection (implementation of requirements), performance assessment and development. This map of sustainability practices provides a unique perspective; hence it distinguishes practices diffused across different supply chain tiers, as well as the mechanism/initiatives employed to diffuse them. The findings suggested that more emphasis was given to environmental practices than social practices. In general, social practices were more related to compulsory level (e.g. human rights) and were evaluated (selection), monitored (performance) and diffused through development (especially educating initiatives) in both 1st tier and 2nd tier. Critical materials suppliers in the 2nd tier were more likely to be engaged by specific procurement teams through the selection, performance and development activities, especially with the aim of meeting compliance and improving performance. The findings also suggested that joint initiatives with critical industrial suppliers focused more on environmental practices. Diffusion of innovation theory was applied to consider different elements that have not been covered in the literature, for instance, emphasis on communication channels and social system elements. The rate of adoption of sustainability practices was directly affected by supporting suppliers in measuring and collaborating in implementing improvements plans, as well as intense educating initiatives. DoI provides a powerful lens to help explain the role of buying firms in the diffusion of sustainability practices. The research provided a more comprehensive view on how sustainability practices were diffused through the supplier selection, performance assessment and development. This work is the first instance of considering intra- and interorganisational factors in the same model for enhancing the diffusion of sustainability practices. Overall, this depicts patterns of the factors and points out the most critical variables influencing the implementation of sustainability practices across the supplier base. This research has the potential to serve as an analysis tool to uncover gaps in activity that could lead to greater adoption of sustainability practices by suppliers, as well as gathering good practice in a structured way.
Keywords: Environmental and social sustainability; sustainability practices; supply chain management activities; supplier sustainability development; diffusion of innovation